Technique for spore production in Cercospora canescens - VINEETA SINGH; CHHATTAR PAL, RAMESH CHAND*, PRABHAT KUMAR, (Indian Phytopathology, 2013)
Cercospora leaf spot caused by Cercospora canescens is the most destructive disease of mungbean. Sporulation of Cercospora spp. in culture media is a general problem. Out of 41 isolates of C. canescens tested for spore production, only 3 produced spore consistently in culture media. Incubation in dark or light did not influence sporulation. A technique for mass spore production was developed by evaluating colonization and sporulation ability of sporulating isolates on substrates like sorghum, maize and wheat grains. Sorghum grains depicted faster colonization (within 20 days) and maximum spore production (9.4 x 105 spores g-1 of grain). The spores on colonized grains were also viable for 2 months at 250C. This grain based inoculum production technique is cheaper and practically feasible. The technique was also validated for other species of Cercospora i.e. C. kikuchii and C. zinniae.